Improving Civics Learning Outcomes Through the Problem Based Learning Model for Elementary School Students - Hartati, Meri; Hong, Dong Anh Chi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This study aims to enhance student learning outcomes by applying the Problem-Based Learning (PBL) model in Civics lessons for class VI.A at elementary school 208 Palembang. Specifically, the research explores how PBL fosters critical thinking, problem-solving, and active student engagement in a subject often perceived as theoretical. Methodology: The study employs Classroom Action Research (CAR), utilizing a cyclical model consisting of four stages: Planning, Implementation, Observation, and Reflection. Data collection methods, including observation, documentation, and tests, are conducted across pre-cycle, cycle I, and cycle II phases, allowing for a comprehensive understanding of PBL's impact on learning outcomes. Main Findings: The results reveal a significant improvement in students' Civics learning outcomes after implementing PBL. The findings indicate growth in individual and collective performance, including increased student engagement, higher minimum and maximum scores, and a notable rise in average scores. These outcomes suggest that PBL effectively nurtures deeper understanding and retention of Civics concepts by encouraging student participation and collaborative problem-solving. Novelty/Originality of this Study: This research's uniqueness lies in its contextual application of PBL in the elementary school setting, specifically within Civics education in Palembang. While PBL has been widely studied in other disciplines, its integration into Civics a subject traditionally taught through rote learning offers fresh insights into how inquiry-based learning models can reshape elementary education. This study demonstrates the potential of PBL to create a more dynamic and interactive learning environment, contributing to pedagogical theory and practice.